The Uses of Refinement, Etiquette and Uncertainty […]: […] in the Autobiographical Writings of Anna Tyutcheva - Kelly, Catriona (Nordlit, 1998)
For reasons that may ultimately derive from the traditional use of exemplary narratives in the schoolroom, feminist history has had a penchant for rebellious heroines, colourful non-conformists who protest against the roles scripted for them by their culture (…).